Results of patient survival after surgical interventions for complicated forms of colon cancer performed in general surgical hospitals - M. A. Kubrak; S. M. Zavhorodnii; M. B. Danyliuk (Patologìâ)
The aim of the study: to evaluate the 1- and 3-year survival of patients operated for complicated forms of colon cancer (СC) in general surgical hospital.